Seaweed and its role in bioremediation- A review - Raj, Rehana; N K, Manju; T S, Fazil; Rangasamy, Anandan; Mathew, Suseela (Fishery Technology, 2022)
Increase in global population has resulted in considerable accumulation of wastes in the environment which eventually reach the surrounding waterbodies. Anthropogenic waste leads to deterioration of water quality, making it unsuitable for further use. The water coming after anthropogenic interference are mostly left out untreated, and may contain contaminants like hydrocarbons, phosphorous, heavy metals, nitrogenous compounds, pesticide residues, dyes etc. The polluted waterbodies are mainly a resultant of various anthropogenic activities which is getting discharged with different treatment levels into the aquatic system. These pollutants are finally getting accumulated in the coastal waterbodies leading to pollution and imbalance to the coastal ecosystem. Bioremediation aims at viable treatment technique which lowers the consequences of this contamination on the environment by employing biological agents, such as bioconcentration and removal using seaweeds. Several research works had reported the efficiency of seaweed in removing these pollutants, nutrients and heavy metals from aquaculture systems, agricultures and urban outflow and industrial effluents. In this chapter, we discuss about the application of seaweed in different ecosystem for removing the effluents and contaminants present in the water bodies and improving the water quality. The technique employed by seaweed for quenching these pollutant compounds from water bodies are also included.